The control of conventionality as protection of women: case study of comparative electoral law: Colombia-Mexico - Marín Gil, Johnny (DIXI, 2022)
Topic: Study on the concept and progress of the concept of conventionality control in light of international human rights law. Likewise, an incipient analysis is made from the comparative law in Colombia and Mexico. Scope: In particular, a contextual and conceptual reasoning of the figure is made through the evolution of the jurisprudence of the Inter-American Court of Human Rights, with the objective of pointing out that such control is nothing more than the jurisdictional concretion of the obligation to guarantee the universal human rights of the global village in the domestic sphere. Characteristics: Colombia is part of the universal fabric. Findings: Civil society is mobilizing and this is the path to change. Conclusions: Conventionality control should not be a fad. In the case of Colombia, an example is the electoral law and the real participation of women.